Dysmagenesemia in critically ill patients: prevalence and nature of magnesium disorder. - Sultan, Shaheen; Gul, Amna; Khalid, Rameesha; Ahsan, Irfan; Khan, Sundus; Waqar Ali, Syed; Naseem, Fahad; Zafar, Khurrum (Pakistan Journal of Kidney Diseases, 2022)
Abstract: Background: Magnesium, ranks on number four for its abundancy in the body. It is known as “the forgotten electrolyte” in the literature. It is second most abundant intracellular cation. Altered magnesium level is frequently encountered electrolyte imbalance in critically ill patients. It increases ICU related morbidity and mortality. Identification and prompt management of magnesium disorder helps in reducing ICU related mortality. Material and methods: we performed a prospective interventional study in which we collected data from intensive care unit of liaquat national hospital. We included only those patients who were having critical illness. We then measured serum magnesium level in all patients and reported the findings. Results: A total of 107 patients from the Medical ICU were included in this study .56 were females (52%) and 51(47.7%) were males. The mean age was 59.6 years. We found that 63.3 % of patients had deranged levels of magnesium. 47.7 % of patients had hypermagnesemia whereas 15.9% of patients had hypomagnesemia. Conclusion: Dysmagenesemia is significantly common in critically ill patient.